2013
DOI: 10.1111/nph.12185
|View full text |Cite
|
Sign up to set email alerts
|

NITRILASE1 regulates the exit from proliferation, genome stability and plant development

Abstract: SummaryNitrilases are highly conserved proteins with catabolic activity but much less understood functions in cell division and apoptosis. To elucidate the biological functions of Arabidopsis NI-TRILASE1, we characterized its molecular forms, cellular localization and involvement in cell proliferation and plant development.We performed biochemical and mass spectrometry analyses of NITRILASE1 complexes, electron microscopy of nitrilase polymers, imaging of developmental and cellular distribution, silencing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In Arabidopsis, changes in the polymer structure and the intracellular localization of Nit1 are closely associated with the transition from proliferation to differentiation (Doskocilová et al, 2013). It is unclear, however, whether the HNE modification of Nit1 causes such changes.…”
Section: How Do Oxylipin Carbonyls Initiate Pcd?mentioning
confidence: 99%
“…In Arabidopsis, changes in the polymer structure and the intracellular localization of Nit1 are closely associated with the transition from proliferation to differentiation (Doskocilová et al, 2013). It is unclear, however, whether the HNE modification of Nit1 causes such changes.…”
Section: How Do Oxylipin Carbonyls Initiate Pcd?mentioning
confidence: 99%
“…Among the other proteins copurifying with DEK3 were the cohesion protein SCC3 involved in mitotic and meiotic cell division (Chelysheva et al, 2005;Schubert et al, 2009) and a putative homolog of the cohesion-associated protein PDS5. Nitrilase1, a multifunctional protein implicated in cytokinesis and in maintaining genome stability (Dosko cilová et al, 2013), was also identified in all experiments. Further, histone deacetylase 3 (HDA3/HDT1) copurified with DEK3, confirming a similar interaction observed in human cells (Hollenbach et al, 2002).…”
Section: Dek3 Association With Topoisomerase 1a and Cohesin Componentmentioning
confidence: 99%
“…Flow cytometry has also been used to sort nuclei prior to transcriptomic analysis [Macas et al, 1998;Zhang et al, 2008;Bourdon et al, 2012] and for cell cycle analysis [Binarová et al, 1993;Kotogány et al, 2010;Petrovská et al, 2012;Doskočilová et al, 2013]. A protocol aimed at yielding suspensions of intact chromosomes [Doležel et al, 1992] is also suitable for the isolation of nuclei; the mild fixation with formaldehyde does not compromise the quality of the DNA in the context of preparing DNA libraries [Šafář et al, 2004;Kasprzak et al, 2006].…”
mentioning
confidence: 99%